On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae) - Fikáček, Martin; Gimmel, Matthew L. (Zootaxa, 2017)
The genus Sternosternus Guillebeau, 1894 was described as an aberrant taxon of the family Phalacridae from Sumatra, based on the unique morphology of its meso- and metaventrite resembling those of Cetonia aurata Linnaeus, 1758 (Guillebeau 1894). It contained the single species, S. grouvellei Guillebeau, 1894, known from a single specimen. The identity of Sternosternus was long unclear, and nothing was published on the genus until Gimmel (2013) studied the type specimen and recognized it actually belonged to the family Hydrophilidae, likely being a member of the genus Dactylosternum Wollaston, 1854.